THE DISPLACEMENT IN DERRIDA’S CONCEPT OF THE “PERFORMATIVE”: FROM THE ITERABILITY OF WRITING TO THE SINGULARITY OF JUSTICE - Manrique, Carlos A. (Princípios: Revista de Filosofia (UFRN), 2015)
This paper retraces two crucial displacements in the history of the notion of the “performative” in Derrida’s thought, and the effects of this notion in his attempt to rethink the contours of ethical and political action, and of the “subject” of this action. First, Judith Butler’s distinctive appropriation of the notion of “iterability” employed by Derrida to describe the performative force of writing, and of language in general. And second, Derrida’s own re-modulation of the notion of the “performative”, in his late reflections on the aporetic structure of “decision” through which he attempts to reflect on the breach between “justice” and “normativity”. Through an examination of the differences at stake in these two possible trajectories for thinking the “performativity” of language and selfhood the paper tries to show, first, the connection between Derrida’s early analysis of “writing” and his late reflections on the gap between “justice” and normativity; and second, it attempts in a rather preliminary way to understand why Derrida, in his attempt to re-think ethical and political action in this way, re-opens a certain “religious” register constitutive of this action, a register, we suggest, connected to the problem of affectivity.